Novel piperazine-chalcone hybrids and related pyrazoline analogues targeting VEGFR-2 kinase; design, synthesis, molecular docking studies, and anticancer evaluation - Marwa F. Ahmed; Eman Y. Santali; Radwan El-Haggar (Taylor & Francis Group, 2021)
New piperazine-chalcone hybrids and related pyrazoline derivatives have been designed and synthesised as potential vascular endothelial growth factor receptor-2 (VEGFR-2) inhibitors. The National Cancer Institute (NCI) has selected six compounds to evaluate their antiproliferative activity in vitro against 60 human cancer cells lines. Preliminary screening of the examined compounds indicated promising anticancer activity against number of cell lines. The enzyme inhibitory activity against VEGFR-2 was evaluated and IC50 of the tested compounds ranged from 0.57 µM to 1.48 µM. The most potent derivatives Vd and Ve were subjected to further investigations. A cell cycle analysis showed that both compounds mainly arrest HCT-116 cell cycle in the G2/M phase. Annexin V-FITC apoptosis assay showed that Vd and Ve induced an approximately 18.7-fold and 21.2-fold total increase in apoptosis compared to the control. Additionally, molecular docking study was performed against VEGFR (PDB ID: 4ASD) using MOE 2015.10 software and Sorafenib as a reference ligand.